An Adaptive Simultaneous Multi-Protocol Extension of CRAFT - Louis Moreau; Emmanuel Conchon; Damien Sauveron (Sensors, 2023)
An exponential number of devices connect to Internet of Things (IoT) networks every year, increasing the available targets for attackers. Protecting such networks and devices against cyberattacks is still a major concern. A proposed solution to increase trust in IoT devices and networks is remote attestation. Remote attestation establishes two categories of devices, verifiers and provers. Provers must send an attestation to verifiers when requested or at regular intervals to maintain trust by proving their integrity. Remote attestation solutions exist within three categories: software, hardware and hybrid attestation. However, these solutions usually have limited use-cases. For instance, hardware mechanisms should be used but cannot be used alone, and software protocols are usually efficient in particular contexts, such as small networks or mobile networks. More recently, frameworks such as CRAFT have been proposed. Such frameworks enable the use of any attestation protocol within any network. However, as these frameworks are still recent, there is still considerable room for improvement. In this paper, we improve CRAFT’s flexibility and security by proposing ASMP (adaptative simultaneous multi-protocol) features. These features fully enable the use of multiple remote attestation protocols for any devices. They also enable devices to seamlessly switch protocols at any time depending on factors such as the environment, context, and neighboring devices. A comprehensive evaluation of these features in a real-world scenario and use-cases demonstrates that they improve CRAFT’s flexibility and security with minimal impact on performance.